The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1600-6143.2010.03151.x
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Mediates Early Graft Failure After Intraportal Islet Transplantation

Abstract: We have previously shown that islet emboli in the portal vein block blood flow and induce local inflammatory reaction, resulting in functional loss of islet grafts following intraportal transplantation. This study was designed to test whether Toll-like receptor (TLR) activation mediates early islet graft failure. Syngeneic islet grafts were transplanted into chemically induced diabetic mice, and TLR deficient mice were used as donors and/or recipients of islet grafts. Islet viability, proinflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…portal vein of the liver together with the transplanted islets (28). Collectively, these studies demonstrate that the anti-HMGB1 mAb 2G7, in comparable dosages and using similar administration routes, confers protective effects in various inflammatory disease models.…”
Section: Discussionmentioning
confidence: 82%
“…portal vein of the liver together with the transplanted islets (28). Collectively, these studies demonstrate that the anti-HMGB1 mAb 2G7, in comparable dosages and using similar administration routes, confers protective effects in various inflammatory disease models.…”
Section: Discussionmentioning
confidence: 82%
“…One mAb recognizing an epitope in the C-terminus of the HMGB1 molecule improved outcome in an experimental stroke model (33). The 2G7 mAb was previously demonstrated to improve survival in a gram-negative sepsis model (29) and to prevent TLR4-mediated early graft failure after pancreatic islet graft transplantation (30).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-HMGB1 mAb (2G7) used in our studies has previously demonstrated beneficial therapeutic effects in models for experimental sepsis and pancreatic islet graft transplantation (29,30). Furthermore, the 2G7 mAb performs excellently in vitro to detect natural HMGB1 in the HMGB1-specific Elispot assay developed by our group (31), in immunohistochemistry studies (32) and to neutralize rHMGB1-induced TNF production in cultured macrophages (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of IL1 receptor antagonist in islets (93), inhibition of TF NF-kB which mediates the detrimental effects of these cytokines on islets (94), inhibition of toll-like receptor 4 and blockade of high mobility group box 1 (HMGB1) with anti-HMGB1 mAb (95) are among the strategies used to inhibit inflammatory cytokines. There is decreased expression of anti-oxidants in pancreatic islets in comparison to most other tissues.…”
Section: Prevention Of Apoptosis Reduction Of the Effects Of Inflammmentioning
confidence: 99%